Quality of life in the course of a one-year use of an advanced hybrid closed-loop system in adults with type 1 diabetes previously naïve to advanced diabetes technology - Cyranka, Katarzyna; Matejko, Bartłomiej; Juza, Anna; Kieć-Wilk, Beata; Cohen, Ohad; Malecki, Maciej T.; Klupa, Tomasz (Frontiers in Endocrinology, 2023)
Aim: To evaluate the effect of a one-year use of an advanced hybrid closed-loop (AHCL) system on the quality of life, level of anxiety and level of self-efficacy in adults with type 1 diabetes (T1D) previously treated with multiple daily injections (MDI) and naive to advanced diabetes technology Methods: 18 participants of a previously published three-month randomized trial (10 men, 8 women; age 40.9 ± 7.6 years) who were switched directly from MDI/BMG to AHCL, completed 12 months of MiniMed 780G™system use (a three-month randomized trial followed by a nine-month follow-up phase). At month six of the study patients were switched from sensor GS3 (Continuous Glucose Monitoring) system, powered by Guardian™ Sensor 3) to GS4.Quality of life was assessed using the Polish validated version of the 'QoL-Q Diabetes' questionnaire. The level of anxiety was evaluated with the use of the State-Trait Anxiety Inventory (STAI). Self-efficacy was assessed with General Self-Efficacy Scale-(GSES).Results were obtained at baseline and at the end of the study.: Significant increase in QoL was reported in the global score (p=0.02, Cohen d=0.61) and in as many as 11 out of 23 analyzed areas of life: Being physically active (p=0.02, Cohen d = 0.71); Feeling well (p<.01, Cohen d = 0.73); Feeling in control of my body (p<.01, Cohen d = 0.72); Looking good (p<.01, Cohen d = 1.07); Working (p<.01, Cohen d = 1.12); Sleeping (p=0.01, Cohen d = 0.66); Eating as I would like (p<.01, Cohen d = 0.79); Looking after or being useful to others (p= 0.02, Cohen d = 0.65); Being active with pets / animals (p<.01, Cohen d = 0.95); Being spontaneous (p=0.02, Cohen d = 0.67); Doing "normal" things (p=0.02, Cohen d = 0.67). Both state (p=0.04, Cohen d = 0.56) and trait (p=0.02, Cohen d = 0.60) anxiety decreased while the general self-efficacy increased (p=0.03, Cohen d = 0.76). No participant stopped the use of the pump.Adults patients with T1D previously treated with MDI and naïve to modern technologies after transition to AHCL system after 12 of treatment experience significant improvement in their psychological well-being.